Temperature measurement of axisymmetric partially premixed methane/air flame in a co-annular burner using Mach–Zehnder interferometry. (November 2015) - Irandoost, M.S.; Ashjaee, M.; Askari, M.H.; Ahmadi, S.
Abstract: In this paper partially premixed laminar methane/air co-flow flame is studied experimentally. Methane–air flame is established on an axisymmetric co-annular burner. The fuel-air jet flows from the central tube while the secondary air flows from the region between the inner and the outer tube. The aim is to investigate the flame characteristics for methane/air axisymmetric partially premixed flame using Mach–Zehnder interferometry. Different equivalence ratios ( φ =1.4–2.2) and Reynolds numbers ( Re =100–1200) are considered in the study. Flame generic visible appearance and the corresponding fringe map structures are also investigated. It is seen that the fringe maps are poorly influenced by equivalence ratio variations at constant Reynolds number but are significantly affected by Reynolds number variations in constant equivalence ratio. Temperatures obtained from optical techniques are compared with those obtained from thermocouples and good agreement is observed. It is concluded that the effect of Reynolds number increment on maximum flame temperature is negligible while equivalence ratio reduction increases maximum flame temperature substantially. Highlights: Partially premixed methane/air co-flow flame was studied experimentally. MZI technique was utilized for temperature measurements. Good agreement was observed for temperature obtained from thermocouple and MZI. Different Reynolds numbers and equivalence ratios were considered. Maximum flame temperature, thermal flame height and fringe patterns were studied.